The effect of oxidation on the flotation properties of a Turkish bituminous coal - Bolat, E; Saglam, S; Piskin, S (ELSEVIER SCIENCE BV, 1998)
It is well known that the behaviour of oxidized coal is different than that of original coal during flotation and that the efficiency of notation differs according to the degree of oxidation. The degree of oxidation of coal particles can be determined based on their surface properties. For this, the electrokinetic potantial measurement is considered to be an efficient method to determine the surface properties of oxidized coal. In this work, based on the zeta potential and flotation data obtained, it can be concluded that the notability of Amasra coal deteriorates on oxidation but can be increased by using electrolytes at low concentrations in the notation media. (C) 1998 Elsevier Science B.V. All rights reserved.
Keywords: flotation properties; bituminous coal; oxidation; OXIDIZED COAL; Chemistry; Energy & Fuels; Engineering